KAJIAN LOYALITAS PELANGGAN DARI PERSPEKTIF KEPUASAN PELANGGAN PASIR CV PUTRA MULIA BATU MERAPI BERBASIS BAURAN PEMASARAN - Ambar Lukitaningsih, Ahmad Dimyathi Atmawijaya & (Universitas Slamet Riyadi, 2017)
This research is done on sand customers in CV Putra Mulia Batu Merapi, oneof the sand mining companies in Klaten district, Central Java province. To know thedirect influence between variables; Product quality, service quality and selling priceto customer satisfaction, and direct influence between variables; Product quality,service quality, selling price to customer loyalty mediated by customer satisfaction.The data used in this study is primary data sourced from the questionnaire, thesample in this study amounted to 60 respondents.The result of the research showsthat: 1) The quality of the product has a positive and significant effect on thesatisfaction, 2) The quality of service has positive and significant effect on thesatisfaction, 3) The price has negative and insignificant effect to the satisfaction, 4)The product quality has negative and insignificant effect to the loyalty, 5) Quality ofservice has positive but insignificant effect on loyalty, 7) Quality of product, servicequality and price simultaneously have positive and significant effect on satisfaction,8) Quality of product, service quality, price And customer satisfactionsimultaneously have a positive but not significant effect on loyalty, 9) Customersatisfaction has negative and insignificant effect on loyalty.Keywords: product quality, service quality, price, satisfaction, loyalty.